2004
DOI: 10.1111/j.1365-2427.2004.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Catchment urbanisation and increased benthic algal biomass in streams: linking mechanisms to management

Abstract: 1. Urbanisation is an important cause of eutrophication in waters draining urban areas. We determined whether benthic algal biomass in small streams draining urban areas was explained primarily by small-scale factors (benthic light, substratum type and nutrient concentrations) within a stream, or by catchment-scale variables that incorporate the interacting multiple impacts of urbanisation (i.e. variables that describe urban density and the intensity of drainage or septic tank systems). 2. Benthic algal biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 46 publications
5
82
1
2
Order By: Relevance
“…Sabater et al [6] found that open nutrient-rich tributaries with warmer temperatures had significantly higher levels of algal biomass than shaded nutrient-poor streams. These results are consistent with other studies that have found interactions of various degrees between light levels, temperature and nutrient levels [5,9,15,16].…”
Section: Introductionsupporting
confidence: 83%
“…Sabater et al [6] found that open nutrient-rich tributaries with warmer temperatures had significantly higher levels of algal biomass than shaded nutrient-poor streams. These results are consistent with other studies that have found interactions of various degrees between light levels, temperature and nutrient levels [5,9,15,16].…”
Section: Introductionsupporting
confidence: 83%
“…Light, climate, geology, land use, substrate size, and vegetation all have been identified as factors that can control algal populations in addition to nutrient conditions and related water chemistry parameters. In some cases, algal biomass and community structure are related more to factors measured at larger scales such as land use (Leland and Porter 2000;Snyder et al 2002;Taylor et al 2004) or patterns in hydrology (Biggs 1996;Biggs and Smith 2002) than to nutrients measured at local and ephemeral scales. Although broad-scale factors have been related to algal biomass and community structure, the hierarchical arrangement of these factors has received less attention (Stevenson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Brooks et al (3) highlighted the considerable biomonitoring challenges to scientists and water resource managers of effluent-receiving streams with ephemeral or seasonally variable flows. Assessing the effects of effluent discharge on the health of receiving waterways is of considerable environmental consequence, especially in catchments with variable stream flows and where population pressure through urbanization and periurbanization is placing increasing pressure upon WWTP infrastructure and the health of freshwater ecosystems (15,39,43).…”
mentioning
confidence: 99%